The International Council of Nurses incidence for the history and socialization of Nursing - Taka Oguisso (Universidad de Alicante, 2012)
The International Council of Nurses (ICN) is a federation of national nurses associations (NNA), created in 1899, by a small group of visionary women, in a milieu of enormous social changes such as industrial revolution and the slavery abolition and with woman's social rights, including the right for voting, social progressivism and healthcare reform. Against all odds, ICN has survived for over 100 years, due to dedication of three women: Ethel Bedford Fenwick, Lavinia Dock y Agnes Karll who created the very first international health professionals organization. The ICN incidence was very instrumental as nursing was just giving its first steps after being institutionalized as a profession by Florence Nightingale. The ICN diffusion and socialization will also benefit the History of Nursing as a field of study. Being the nurses' voice ICN can make their profession to develop and reach out wider geographical boundaries and to learn better their own profession and the nursing professional identity.